An Efficient Fe/H2O Medium in situ Reduction and Cyclization Reaction for the Synthesis of Pyrazolo[3,4-a]acridin-10-one and Pyrazolo[4,3-a]acridin-10-one Derivatives - Xu, Hui; Li, Lei; Lin, Cong; Kou, Wang; Ling, Zhi; Xu, Zhongyun; Rong, Liangce (Synthesis, 2018)
An efficient and simple method for the synthesis of pyrazolo[3,4-a]acridine and pyrazolo[4,3-a]acridine derivatives directly form nitro compounds by in situ reduction and cyclization reaction under Fe/H2O medium is reported. Compared to amino compounds, nitro compounds are more stable and easier to obtain. In addition, because iron is a nontoxic, inexpensive, and environmentally friendly reductant, this method is especially suitable for organic synthesis. The other advantages of this process are cheap raw materials, less pollution, and wide substrate range.
Keywords: in situ reductions; nitro compounds; iron; pyrazolo-[3,4-a]-acridin-10-one; pyrazolo[4,3-a]acridin-10-one